The representation of females in clinical trials for substance use disorder conducted in the United States (2010–19). (27th February 2022) - Gunn, Christine M.; Pankowska, Magda; Harris, Miriam; Helsing, Emma; Battaglia, Tracy A.; Bagley, Sarah M.
Abstract: Background and aims: Women have historically been under‐represented in clinical research, but the extent to which this is true for substance use disorder (SUD) trials is unknown. We aimed to determine the ratio of female:male participation in clinical trials for SUDs and describe the reporting of sex‐specific outcomes from 2010 to 2019. Design: A retrospective cohort review of clinical trials involving people with SUD. Setting: United States. Participants: Clinical trials including people with SUD registered in clinicaltrials.gov and completed between 1 January 2010 and 31 December 2019 were reviewed. Trials were excluded if they had < 30 participants, focused on SUD prevention, were conducted outside the United States and/or did not report data on participant sex or gender. Measurements: The following were extracted for each trial: primary outcome, number of participants enrolled, analytical sample size, percentage of participants who were female, inclusion of transgender participants, whether sex‐based analyses were performed, funding source, type of SUD and type of intervention. Relative representation in trials was examined using the female:male ratio, reported using median ratios and by year of trial completion. The proportion of females participating was adjusted using the underlying disease prevalence among females using National Survey on Drug Use and Health data. Findings: A total of 316 trials met inclusion criteria: 274 were mixed‐sex, 12 enrolled only males and 30 only females. In 274 mixed‐sex trials, 40% of 57 544 participants were female. Only 22 trials (8%) reported any sex‐specific analyses; four studies (1.5%) reported inclusion of transgender participants. Females represented 35% of participants in trials targeting illicit drug use disorder, 52% in nicotine use disorder and 29% in alcohol use disorder. Accounting for underlying disease prevalence revealed that women had the lowest relative enrollment in alcohol use disorder trials (median participation to prevalence ratio in 2017: 0.58; 95% confidence interval: 0.13, 0.91). Conclusions: A review of 316 US clinical trials for alcohol, nicotine and illicit substance use disorders completed between 2010 and 2019 showed that females were enrolled at lower rates than males overall. Only 8% of the trials reviewed reported sex‐specific analyses and 1.5% reported transgender participants.